Adam 2.0 - Catarino, Jorge, 1985- (2013)
Contém: Turing, von Neumann and Wiener - tawards a new taxonomy of man. The human being as a functional model. Between the exteriority of the machine and the prosthetic incorporation. The cyborg: symbiosia as thge new paradigm of the absence of paradigm